Cooperation between the United Nations and the European Union in the fields of peacekeeping and crisis management in unpredictable times - Mihaela-Adriana Pădureanu (European Institute of Romania, 2022)
The United Nations and the European Union have been working together since 2003 in the areas of peace operations and crisis management. They cooperate in regions such as the Western Balkans, Africa, and the Middle East. As the main representatives of the most important global and regional organizations, the UN and the EU aim to deploy efficient and fast responses to different types of crises such as: civilian, political, or institutional. In September 2018, they identified eight priorities to be addressed in the framework of the UNEU Strategic Partnership on Peacekeeping and Crisis Management for 2019-2021, stressing especially the importance of women for peace, and security. Then, two years later, in September 2020, during the 75th session of the UN General Assembly, they signed the Framework Agreement on Mutual Support in the context of their respective missions and operations in the field. In this working paper, we use primary sources such as official documents, interviews, and declarations to look at how this relationship has developed, and to assess the main implications of the partnership for the parties concerned and its main beneficiaries.
Keywords: 330; UN; EU; peacekeeping; crisis management; cooperation